Artificial Intelligence in Connectivism Learning: A Pathway to Communication Skill Development - Newbegin Sugandhamani; Ramkumar Emaraj Vairamuthu; Lincy Kiruba Selvaraj (Tecno Scientifica Publisher, 2026)
Communication skills have grown in importance across academic, professional, and social settings, but the current instruction of communication skills has often lacked personalization, adaptability, and an effective feedback system. Given these constraints, connectivism theory broadened the notion of learning into a networked and relational process with a strong focus on both human and technological relationships in relevant contexts, particularly in digital learning environments. Hence, this study concentrated on the utilization of Artificial Intelligence (AI) tools such as conversational chatbots, speech-recognition software, and automated writing evaluation systems to improve communication skills. The study was carried out using a mixed-methods research design composed of quantitative and qualitative analyses. Pre-test and post-test evaluations, along with learner feedback, were used to collect data, as well as AI- and peer-based assessments of learners who participated in communication training sessions supported by AI tools. This study compared the transformation of learners’ fluency, vocabulary, pronunciation, coherence, and engagement within the AI-connectivism learning framework. The results showed significant improvements in students’ communication skills as a result of regular interaction with AI-enhanced tools and collaborative learning groups. Reflection, critical thinking, and meaningful communication practice were crucial components of the learning process, highlighting the indispensable role of teachers and peers in the classroom. AI technologies provided immediate feedback, personalized practice, and adaptive learning opportunities. According to the study, the integration of AI within a connectivist educational context was found to be flexible and scalable for communication skills development in the modern educational environment.